Whole genome characterization of non-tissue culture adapted HRSV strains in severely infected children - Kumaria, Rajni; Iyer, Laxmi Ravi; Hibberd, Martin L; Simões, Eric AF; Sugrue, Richard J (Virology journal, 2011)
Background Human respiratory syncytial virus (HRSV) is the most important virus causing lower respiratory infection in young children. The complete genetic characterization of RSV clinical strains is a prerequisite for understanding HRSV infection in the clinical context. Current information about the genetic structure of the HRSV genome has largely been obtained using tissue culture adapted viruses. During tissue culture adaptation genetic changes can be introduced into the virus genome, which may obscure subtle variations in the genetic structure of different RSV strains. Methods In this study we describe a novel Sanger sequencing strategy which allowed the complete genetic characterisation of 14 clinical HRSV strains. The viruses were sequenced directly in the nasal washes of severely hospitalized children, and without prior passage of the viruses in tissue culture. Results The analysis of nucleotide sequences suggested that vRNA length is a variable factor among primary strains, while the phylogenetic analysis suggests selective pressure for change. The G gene showed the greatest sequence variation (2-6.4%), while small hydrophobic protein and matrix genes were completely conserved across all clinical strains studied. A number of sequence changes in the F, L, M2-1 and M2-2 genes were observed that have not been described in laboratory isolates. The gene junction regions showed more sequence variability, and in particular the intergenic regions showed a highest level of sequence variation. Although the clinical strains grew slower than the HRSVA2 virus isolate in tissue culture, the HRSVA2 isolate and clinical strains formed similar virus structures such as virus filaments and inclusion bodies in infected cells; supporting the clinical relevance of these virus structures. Conclusion This is the first report to describe the complete genetic characterization of HRSV clinical strains that have been sequenced directly from clinical material. The presence of novel substitutions and deletions in the vRNA of clinical strains emphasize the importance of genomic characterization of non-tissue culture adapted primary strains.